The Relationship Between Parents Perceptions And The Completeness Of Basic Immunization In Infants Aged 12-24 Months At Posyandu Sakura Air Upas, Ketapang Regency, West Kalimantan Province In 2022 - Sutrisni; Dewi Kartika Sari; Eka Lilyanti (Journal of Global Research in Public Health, 2023)
Immunizations is the on of the preventive efforts carried out by the government in preventing schildren from infectious diseases. The coverage of UCI villages or ward according to the Community Health Center in Ketapang Regency in 2021, the Air Upas Health Center is in 7th place (75% coverage) which has not met the target. As for immunization coverage complete basic measles and basic immunization in infants from Ketapang Regency, Air Upas was ranked 13th, namely the fulfillment of measles immunization by 73% and basic immunization by 74%. There are many reasons why they don’t immunize their babies. The purpose of this study was to analyze the relationship between parents perceptions and the completeness of basic immunizations in infants aged 12-24. The research is a type of korelasional analytic design. The population in this study were parent who had babies aged 12-24 months. The sampling technique uses total sampling where the number of samples is the same as the population which later the population that enter is the same as the number of samples needed, namely as many as 33 people. Data were collected using questionnaires and basic immunization completeness assessment sheets, and then analyzed using chi-square statistical analysis with p < 0,05. The results of the analysis most of the respondents (60,6%) had positive perceptions, and 18 respondents (54,5%) or most of them had babies with complete immunization. The results of the statistical test using che-square show the results of the value X2 – 18,992a and p = 0,000 the value of p < α where p < 0,05 means that the results showed that parent had a positive perception of basic immunization in infants aged 12-24 months. Researches hope that health workers will continue to increase their motivation, ability, and knowledge related to complete basic immunization. In addition, it can increase education about complete basic immunization and the importance of completeness of basic immunization for Posyandu cadres, parents and families so that it can increase immunization coverage and change negative parental perceptions of immunization for infants.